THU0458 MPV and RDW: Subclinical Inflammation Markers in Attack-Free Familial Mediterranean Fever (FMF) Patients. (23rd January 2014) - Cetin, G. Y.; Gul, O.; Kesici-Metin, F.; Gokalp, I.; Sayarlioglu, M.
Abstract : Objectives: Mean platelet volume (MPV) and red cell distribution width (RDW), as a marker of inflammation, have an important role in several chronic inflammatory disorders like familial Mediterranean fever (FMF). Many studies have shown that subclinical low grade inflammation persisted during attack free periods in FMF patients. We aimed to investigate whether RDW and MPV values differ between patients with FMF during attack free periods and healthy controls. Methods: In this study, 89 patients (Male/Female: 30/59, mean age:31, 8±10) with FMF during attack-free periods and 30 age, sex-matched healthy controls (Male/Female:10/20, mean age:31, 4±5, 7) were enrolled. Erythrocyte sedimentation rate, C-reactive protein, white blood cell count, platelet count, hemoglobin, MPV and RDW levels were retrospectively recorded. The patients were evaluated in accordance with Tel-Hashomer Severity Scoring which includes six elements, including diseases onset age, dose of colchicum, number of involved sites in one attack and during the course of the disease, and the presence of pleuritic and erysipelas-like erythema. Results: Mean age, male/female ratio and the mean levels of hemoglobin, white blood cell count were similar in two groups. RDW, platelet counts were significantly higher and MPV was significantly lower and in patients with FMF group (%15, 59±1, 6 vs %12, 9±0, 8 p<0, 001, 289±78, 2 K/uL vs 245, 63±55, 7 K/uL p=0, 005 and 7, 9±1 fL vs 9, 4±0, 9 fL p<0, 001 respectively ). In attack-free FMF group negative correlation has been found between the MPV and RDW values (p<0, 001, r=-0, 40). Conclusions: Our results suggest that low MPV and high RDW levels may provide additional information about persisted subclinical inflammation in FMF patients during attack-free periods. Disclosure of Interest: None Declared